Profit Tax Competition and Formula Apportionment - Rüdiger Pethig; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2003)
We analyse tax competition with corporate income taxes in a common market where tax revenues are allocated according to an apportionment formula. Generally, tax competition is sharper (i.e., equilibrium tax rates are lower) the more tax-elastic is the apportionment formula. This depends on the properties of production technologies. In particular: (i) With fixed labour input, tax competition is sharpest if apportionment is based on property-shares, followed by the sales- and payroll-shares. (ii) If capital and labour are endogenous and technologies are Cobb-Douglas, tax competition under the property- and the payroll-share rule is sharper than under the sales-share formula. Factor elasticities determine whether payroll- or property-share apportionment generates sharper tax competition.
Keywords: D21; D81; 330; tax competition; formula apportionment